Evaluation of Various Technology Solutions to Address Riverside Construction Problems: Examining Technological Solutions for Riverside Construction Challenges (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Modern technology introduces a variety of bridges to help with the challenge of crossingrivers. A bridge is a building designed to cross a physical barrier (such a body of water, valley, road, orrail) without obstructing the path below. It is designed to allow passage over the obstruction, which istypically something that would be difficult or impossible to cross otherwise. Construction of Bridgesmain challenge is how to construction the foundation in to the river. The objective of current research isto use a variety of technology to research and analyze the river flow at the tidal influence. Variousmanagement strategies are proposed to overcome difficulties in building bridges across rivers